ANALYSIS OF INPUT INDICATORS OF THE SPHERE OF HIGHER EDUCATION OF KAZAKHSTAN (EDUCATION IN THE 21ST CENTURY, 2023)
The temporal and spatial distribution of the current challenges in the field of higher educationmanagement shows that these same challenges can be solved through joint efforts that do notcontradict international trends in the development of the education sector. The effectiveness of thesearch for common solutions in the field of education has been proven over the course of a decade,as it also becomes clear that spatial, economic, political, cultural and other factors can be the basisof unity. It is this complex of factors that underlies the formation of the EAEU. Cooperation of theEAEU member states in the field of education has new prospects - not all aspects of thiscooperation have been identified and are operating in the current period.Of particular importance is the study of the educational traditions of societies representingdifferent cultures of the EAEU member states, the contours of new dialogues. From this point ofview, it is especially important not only to study the Russian education sector, which is completelyopen for cooperation in the Armenian education sector, but also to study the Kazakhstanieducation experience, which is possible in terms of identifying new educational and culturalinteractions.Cooperation between the EAEU member states has not yet achieved final success in the fieldof education, which requires new research.If the volume of cooperation between Armenia and Russia, the underlying factors andperspectives are clearer, the same is difficult to say about Kazakhstan. As EAEU member states,apart from examples of private cooperation in the field of education, the ways of cooperation in thefield of higher education management have not been expanded and clarified, especially betweenKazakhstan and Armenia.This study aims to facilitate the search for cooperation in the field of education managementin the EAEU member states.218The purpose of the study is to identify the specifics of the indicators of the input ofKazakhstani higher education from the EAEU member states using a specially developedmethodology.As part of the study, a new methodology for the comparative analysis of the higher educationsystems of the EAEU member states was developed, within the framework of which indicatorswere developed for the first time, thanks to which it is possible to evaluate and analyze the featuresof education management.
Keywords: Higher education, education management, EAEU member states, the education system of Kazakhstan, input indicators, education development.